Synthesis of Benzophenones and in vitro Evaluation of Their Anticancer Potential in Breast and Prostate Cancer Cells. (24th April 2019) - Saidi, Lydia; Rocha, Djenisa H. A.; Talhi, Oualid; Bentarzi, Yamina; Nedjar‐Kolli, Bellara; Bachari, Khaldoun; Almeida Paz, Filipe A.; Helguero, Luisa A.; Silva, Artur M. S.
Abstract: Breast and prostate cancers are frequently treated with chemotherapy. Several novel chemicals are being reported for this purpose, particularly synthetic and natural benzophenones. This work reports the synthesis of substituted 2‐hydroxybenzophenones through 1, 4‐conjugate addition/intramolecular cycloaddition/dehydration of nitromethane on key intermediate chromones. Structures were extensively studied by means of 2D NMR spectroscopy and single‐crystal XRD. Their cytotoxicity was evaluated in vitro in two breast cancer cell lines (MDA‐MB‐231 and T47‐D) and one prostate cancer cell line (PC3). The most potent compound exhibited good cytotoxic effects against the three cancer cell lines (IC50 values ranging from 12.09 to 26.49 μm ) and induced cell‐cycle retardation only on prostate cancer cells, which suggested that it might exert cell‐type‐specific effects. Abstract : Bring on the subs ! Substituted 2‐hydroxybenzophenones are synthesized in a one‐pot tandem reaction and screened for anticancer activity against breast and prostate cancer cell lines. The compound with chloro and methyl substituents exhibits cytotoxic effects against MDA‐MB‐231, T47‐D, and PC3 cancer cells, with IC50 values ranging from 12.09 to 26.49 μm . This compound also induces cell‐cycle retardation and an increase in cell death by cytotoxic effects in PC3 cells.